Optimal decay rate of the two-fluid incompressible Navier–Stokes–Fourier–Poisson system with Ohm's law. (February 2022) - Gong, Weihua; Zhou, Fujun; Wu, Weijun; Hu, Qian
Abstract: This paper is to investigate the optimal L p ( p ≥ 2 ) time decay rate of global solutions to the two-fluid incompressible Navier–Stokes–Fourier–Poisson system with Ohm's law. The result shows that the time decay rate of this system achieves the same as that of the incompressible Navier–Stokes equation, in other words, the coupling of the self-consistent Poisson equation does not change the decay rate of the incompressible Navier–Stokes equation. This phenomenon is interesting, compared to the compressible Navier–Stokes equation, whose time decay rate decreases when it is coupled with the self-consistent Poisson equation.